The Model of Leadership Style and Work Productivity - Syafri, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The purpose of this study was to determine (1) the effect of leadership of the Head of the West Java Provincial Education Office on the work productivity of employees of the West Java Provincial Education Office; (2) the effect of employee discipline on the work productivity of employees of the West Java Provincial Education Office; and (3) the effect of leadership and employee discipline on the work productivity of employees of the West Java Provincial Education Office. The research method used is descriptive and explanatory survey method using a sample of West Java Provincial Education Office employees as respondents, totaling 50 people. Based on the results of the study, the research results show that leadership in the West Java Provincial Education Office is generally good, but there are several things that need attention, namely the lack of smooth communication between employees and leaders, a less conducive work atmosphere, less attention to employee conditions and unclear task structures; employee discipline is considered quite good, but it is necessary to improve discipline, namely punctuality of attendance, obedience in following SOPs, and responsibility in maintaining work infrastructure; leadership affects employee work productivity, where the better leadership will result in better work productivity of employees of the West Java Provincial Education Office; discipline affects employee work productivity, so that the higher employee discipline, the higher work productivity will be; and leadership and employee discipline together affect employee work productivity, but when viewed partially it turns out that leadership is more dominant in influencing employee work productivity than employee discipline.